An Analytical Framework for Assessing the Effect of Income from Non-timber Forest Products on Poverty Alleviation in Savannah Region, Sudan - Adam, Yahia Omar; Pretzsch, Jürgen; Pettenella, Davide (University of Khartoum Journal of Agricultural Sciences, 2023)
The study objective was to develop an analytical framework to assess the effect of income from non-timber forest products (NTFPs) on poverty alleviation in the Savannah region of Sudan. The study developed a conceptual framework based on a production-to-consumption system. A framework was developed from the analysis of three case studies selected from the Savannah region of Sudan based on their economic value. The framework considered income from NTFPs to be influenced by resource base, markets for the products and households’ characteristics within the political environment. The effect on poverty alleviation was achieved by the potential traded products through the creation of capital invested in other livelihood activities. The developed framework could potentially be of direct value to assess the impact of income from NTFPs on poverty alleviation in the Savannah region. It also directs decision makers and development planners to focus on those NTFPs with the highest capacity for poverty alleviation; and to diagnose factors influencing the NTFPs financial returns. Research on other NTFPs from different areas within the Savannah region is highly recommended to facilitate comparison and generalization.